Patients' experiences attributed to the use of Passiflora incarnata: A qualitative, phenomenological study. (1st March 2019) - Canella, Claudia; Bachmann, Christoph; Wolfensberger, Balz; Witt, Claudia M.
Abstract: Ethnopharmacological relevance: Passiflora incarnata Linnaeus ( Passiflora incarnata ) was established as a medicinal plant in Europe in the middle of the 19th century. Since then, it has been used for the treatment of anxiety, sleep disorders and restlessness in Western European phytotherapy. This study provides insights into how Passiflora incarnata is currently used and experienced as a medicinal plant by German-speaking patients in Switzerland. Aim: This qualitative study aimed to explore patients' experiences and the values, views and interpretive processes that formed their perceptions of the use of an ethanolic extract of Passiflora incarnata . Methods: A total of 8 patients participated in this exploratory, qualitative observational study. The patients filled in pre- and posttreatment questionnaires, kept diaries and were interviewed in a face-to-face setting. For the data analysis, descriptive statistics, qualitative content analysis, narrative inquiry and documentary methods were applied. Results: This is the first qualitative study of patients' real-life experiences with an ethanolic extract of Passiflora incarnata . We identified three distinct types of patient biographical narratives attributed to different experiences when using Passiflora incarnata . Patients with type 1 narratives described moving from a performance orientation to resetting priorities and attaining calmness. Patients with type 2 narratives maintained a performance orientation while adopting calmness. Patients with type 3 narratives maintained a performance orientation and suffered from persistent illness. Conclusion: The distinct biographical narratives of the patients associated with their specific experiences of taking Passiflora incarnata provide an additional perspective on the use of Passiflora incarnata as a medicinal plant. Graphical abstract: Three types of patient biographical narratives attributed to the experiences of using Passiflora incarnata